Tourism Management for Multi-Cultural Based Tourism Destination in China - Chuanchen BI (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
China is the country with variety ethnic groups and cultures, besides the majorHan group and its ‘Han culture’, 55 ethnic groups have their unique and charmingculture and traditions as well. With the development of tourism industry, especiallyafter the moving into the mass tourism era in 2015, how to develop the tourismindustry facing the multiculturalism demands become serious to be focused.Xishuangbanna region as the habitat where more than 14 different cultural locatedbecomes the popular tourism destinations since 1953. Due to the multi-ethnic groupswith different traditional festivals and traditional way of life, the tourism industryachieved its commercial summit in 2002-2004. The cultural based tourism is theselling points and most attractive point in Xishuangbanna region, this research focuson the management of certain tourism management and trying to explore themanagement model for multi-cultural based tourism in Xishuangbanna region. Inorder to achieve the objectives of this study, field survey with participatoryobservation and in-depth interview, and systematic review are applied. The findingsof this paper indicated for developing the multi-cultural based tourism and movingtowards the commercial success, the authenticity with multi-stakeholdersparticipatory should be kept in the priority to be focused. The ‘tourism company +local community’ is discovered for the multi-cultural based tourism management inXishuangbanna region, as it could not only improve the living standard for the localresidents, also provide the opportunity for multi-stakeholders participate in thetourism management and development.Keywords: Multi-cultural tourism management, authenticity, ‘tourism company+ localcommunity’ management, stakeholder, Xishuangbanna region